Incorporating Information of microRNAs into Pathway Analysis in a Genome-Wide Association Study of Bipolar Disorder - Shih, Wei-Liang; Kao, Chung-Feng; Chuang, Li-Chung; Kuo, Po-Hsiu (Frontiers in Genetics, 2012)
microRNAs (miRNAs) are known to be important post-transcriptional regulators that are involved in the etiology of complex psychiatric traits. The present study aimed to incorporate miRNAs information into pathway analysis using a genome-wide association dataset to identify relevant biological pathways for bipolar disorder (BPD). We selected psychiatric- and neurological-associated miRNAs (N=157) from PhenomiR database. The miRNA target genes predictions were obtained from microRNA.org. Canonical pathways (N=4,051) were downloaded from the Molecule Signature Database. We employed a novel weighting scheme for miRNA target genes in pathway analysis using methods of gene-set enrichment analysis and sum-statistic. Under four statistical scenarios, 38 significantly enriched pathways (P-value <0.01 after multiple testing correction) were identified for the risk of developing BPD, including pathways of ion channels associated (e.g., gated channel activity, ion transmembrane transporter activity, and ion channel activity) and nervous related biological processes (e.g., nervous system development, cytoskeleton, and neuroactive ligand receptor interaction). Among them, 19 were identified only when the weighting scheme was applied. Many miRNA-targeted genes were functionally related to ion channels, collagen, and axonal growth and guidance that have been suggested to be associated with BPD previously. Some of these genes are linked to the regulation of miRNA machinery in the literature. Our findings provide support for the potential involvement of miRNAs in the psychopathology of bipolar disorder. Further investigations to elucidate the functions and mechanisms of identified candidate pathways are needed.